Grad Ready: Enhancing graduate readiness through intelligent mobile application - Hanan ALOTAIBI; Shireen S. SAIFUDDIN (Revista Română de Informatică și Automatică)
Graduates experience significant challenges when moving from academic environments to the job market. The issues include a shortage of practical experience, a disparity between their academic knowledge and companies’ requirements, struggles with resume building, and challenges in job searching. The application designed to facilitate the graduates’ transition into the job market is called “The Grad Ready”. It is an intelligent mobile app that bridges the gap between academic knowledge and the professional skill requirements for computer science graduates using matching algorithms to enable companies to target and recruit them. The Waterfall software development methodology was used for it. The requirements were determined by conducting a survey with students ready to graduate from the computer science department. Following the design, implementation, and testing phases, the application was successfully completed, resulting in the development of a user-friendly and intelligent solution meeting all the intended goals and performance criteria.